Global consensus for the screening, diagnosis, staging, treatment, and surveillance of ovarian cancer in areas of significant resource limitations: report from the International Gynecological Cancer Society consensus meeting - Maluf, Fernando; Helber, Henrique A.; Tostes, Francinne; Maluf, Ligia A.; Helito, Juliana K.; Moretti-Marques, Renato; Dal Molin, Graziela Z.; Azevedo, Bruno Roberto B.; Ortiz, David I.; Cantu, David; Silva Filho, Agnaldo L.; Nogueira-Rodrigues, Angelica; et al. (Frontiers in Oncology, 2026)
IntroductionThe objective of this consensus report is to provide practical, resource-stratified recommendations for the management of ovarian cancer in countries with limited resources, where direct application of international guidelines is often difficult. To address these challenges, recommendations were developed from a panel of international experts.MethodsThe panel met in New York in September/October 2022 during the International Gynecological Cancer Society congress and was composed of specialists from countries in Africa, Asia, Eastern Europe, Latin America, and the Middle East. The panel addressed 72 questions and provided recommendations for the diagnosis, staging, treatment, and surveillance of ovarian cancer. Consensus was defined as at least 75% of the voting members selecting a particular recommendation, whereas a majority vote was considered when one option garnered between 50% and 74.9% of votes. Resource limitation was defined as any issues limiting access to qualified surgeons, contemporary imaging or radiation-oncology techniques, antineoplastic drugs, or funding for providing modern medical care.ResultsConsensus was reached for 10 out of 72 (13.9%) questions presented to the panel, whereas a majority vote was reached for 26 (36.1%) additional questions. For the remaining questions, there was considerable heterogeneity in the recommendations.ConclusionThe development of guidelines focusing on areas facing more severe resource limitations may improve medical practice and patient care.